1983
DOI: 10.1520/jfs12243j
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Stability of Benzodiazepines in Blood and Tissues

Abstract: The stability of benzodiazepines in blood and tissues was examined in this study. Specifically, diazepam, chlordiazepoxide, flurazepam, and their desalkyl metabolites were studied over several months. Diazepam, flurazepam, and N-1-desalkylflurazepam were stable when stored in blood at room temperature while chlordiazepoxide, norchlordiazepoxide, and nordiazepam were found to be unstable under similar storage conditions. Data from tissues containing these chemicals corroborated the results from blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 4 publications
3
16
0
Order By: Relevance
“…Thus, precautions should be taken against potential decomposition of drugs during storage, which may lead to disagreements between the results of the primary and subsequent examinations due to various reasons, including the direct and secondary effects of bacteria www.elsevier.com/locate/forsciint Forensic Science International 174 (2008) [189][190][191][192][193][194][195][196] propagation. Although there have been several studies about such effects of bacteria [3,[5][6][7], there is a pressing need for the comprehensive investigation that covers various types of drugs and metabolites in urine, and preservative measures against their decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, precautions should be taken against potential decomposition of drugs during storage, which may lead to disagreements between the results of the primary and subsequent examinations due to various reasons, including the direct and secondary effects of bacteria www.elsevier.com/locate/forsciint Forensic Science International 174 (2008) [189][190][191][192][193][194][195][196] propagation. Although there have been several studies about such effects of bacteria [3,[5][6][7], there is a pressing need for the comprehensive investigation that covers various types of drugs and metabolites in urine, and preservative measures against their decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Specific stability studies of several forensically important drugs in blood and other fluids or tissues have been published including cocaine, its metabolites and its degradations product in whole blood, post-mortem blood or plasma [32,37,45,46], benzodiazepines, antidepressants, antipsychotics, analgesics and/or hypnotics in whole blood, plasma or post-mortem blood [29,30,43,[47][48][49][50][51], morphine and/or its glucuronides and/or buprenorphine in whole blood, plasma or post-mortem blood [31,33,52], 11-nor-Δ 9 -carboxy-tetra-hydrocannabinol glucuronide (THCCOOglu) in plasma [38,53], toluene and acetone in liver, brain and lungs [39], 3,4-methylenedioxymethamphetamine (MDMA), 3,4-methylenedioxyethylamphetamine (MDEA) and 3,4-methylene-dioxyamphetamine (MDA) in whole blood [34], carbon monoxide in post-mortem blood [54], GHB in blood, serum or post-mortem blood [44,55,56] and ethanol in whole blood, plasma, post-mortem blood or vitreous humor [40,57,58].…”
Section: Stability Investigations Of Drugs In Biological Specimensmentioning
confidence: 99%
“…In 1983 it was found that diazepam was stable with nordiazepam, flurazepam and N-1-desalkylflurazepam being moderately stable with only 'minor' losses (\20%) in blood and tissues [52]. Chlordiazepoxide and norchlordiazepoxide on the other hand were found to rapidly degrade to various metabolites.…”
Section: Benzodiazepinesmentioning
confidence: 99%
“…Chlordiazepoxide and norchlordiazepoxide on the other hand were found to rapidly degrade to various metabolites. Norchlordiazepoxide was initially converted to demoxepam, which then further degraded to form nordiazepam-both of which are produced ante-mortem in the body during metabolism [52]. In the work by Stevens using putrefying liver tissue, demoxepam was again found to be converted to nordiazepam, with chlordiazepoxide forming a desoxy-product [44].…”
Section: Benzodiazepinesmentioning
confidence: 99%
See 1 more Smart Citation